Relation of Relationship Between Research Theory and Variable with Management Case Study - Alwiyah, Alwiyah; Louangdy, Toto Thinakone; Yolandari, Aulia (APTISI Transactions on Management (ATM), 2018)
In a management at Higher Education in conducting a scientific work research is a very important step, especially regarding the relationship between theory and research variables. On the provisions that have been applied to management in the previous Higher Education where the scientific work studied is not directed because there is no clear object variable. In this study review the subject matter of theory, components, and theoretical descriptions, concepts and constructs, understanding variables, with the results of research on various variables such as independent and dependent variables, intervening variables, moderator variables, and control variables, operational definitions, theoretical frameworks and frame of mind in research. by using 2 (two) research methods, namely direct observation on the results of student research, and the literature review described in the following study. So that it is expected that the existence of theory and variable research on management at the Higher Education can make scientific work more focused. Keywords: Research Theory, Research Variables, Management.